Methodology to Define an Overall Efficiency of Photovoltaic Inverters Considering Static and Dynamic Tests - Henrique Horst Figueira; Fernando S. Scherer; Ricardo J. F. Bortolini; Lucas Vizzotto Bellinaso; Leandro Michels (Eletrônica de Potência)
Efficiency indices for inverters have been developed with the increasing adoption of photovoltaic (PV) systems. The European and Californian efficiencies are widely recognized, focusing on static inverter operation. Standards such as EN50530 and IEC 62891 introduced dynamic efficiency tests considering irradiance variations, but without a methodology to weigh the efficiencies within a single index. To address this gap, our study proposes a methodology to define an overall efficiency considering both static and dynamic inverter operation. Irradiance data with sub-minute sampling is classified into irradiance and irradiance derivative ranges. Then, weights for static and dynamic efficiency tests are obtained, and less significant ones are discarded. The results were applied to three PV inverters tested in the laboratory. By eliminating the less significant tests, the number of dynamic tests was reduced from 30 to 10. In two of the inverters, the inclusion of dynamic tests resulted in a 2% reduction in overall efficiency compared to the static. An overall efficiency index is relevant for better comparing different PV inverters, especially when considering dynamic behaviors. This index may be significant for the PV market, governmental energy efficiency programs, and inverter manufacturers, providing guidelines to enhance the efficiency of their products.